Impact of an Educational Intervention Aimed at Nursing Staff on Oral Hygiene Care on the Incidence of Ventilator-Associated Pneumonia in Adults Ventilated in Intensive Care Unit - Sánchez Peña, Melissa; Orozco Restrepo, Luz Angélica; Barrios Arroyave, Freddy Andrés; Suárez Brochero, Oscar Felipe (Investigación y Educación en Enfermería, 2021)
Objective. This work sought to evaluate the impact of an educational intervention on oral hygiene care aimed at nursing care staff, on the incidence of Ventilator-Associated Pneumonia (VAP) in adults from an ICU in Colombia. Methods. Quasi-experimental study pre- and post-educational intervention aimed at nursing staff in which theoretical-practical sessions were conducted during 12 weeks to explain different oral hygiene techniques according to the oral conditions of patients. The study gathered sociodemographic, clinical, and characteristic variables of the oral and dental care received. The VAP was diagnosed according with international criteria. Results. The educational intervention received participation from 60 individuals (40 nurses and 20 nursing aides), 80% were women. The work collected data from 171 patients, 70 (40.9%) cared for after the educational intervention. Daily oral and dental care by the staff increased from 29.6% to 92.8% after the intervention. Although the accumulated incidence of VAP diminished from 8.9% to 2.8% and the rate of incidence dropped from 9 to 3.5 cases per 1000 days of intubation, these changes were not statistically significant. Conclusion. The educational intervention aimed at the nursing staff in oral care reduced the incidence of VAP in adults connected to ventilator in ICU; although this decrease was not statistically significant, it was a clinically relevant result for the institution, which is why it is necessary to continue the educational strategies on oral health studied in this staff.